Adding motility stimulants to improve freezing of buffalo sperm recovered from epididymal Cauda - Camargos, Aline Sousa [UNESP]; Oba, Eunice [UNESP]; Monteiro, Gabriel Augusto [UNESP]; Fabres, Yamê [UNESP]; Silva, Robaina Sancleir [UNESP]; Zorzetto, Mariana [UNESP]; Maziero, Rosiara Rosária Dias [UNESP]; Papa, Frederico Ozanam [UNESP]; Ramos, Alcides Amorim [UNESP] (My University, 2013)
The cryopreservation of epididymal sperm is important to preserve genetic material from valuable buffalo bulls. This study evaluated the viability of post-thawed sperm samples recovered from the epididymal cauda adding motility inductors. For that, were used epididymides from eight Murrah buffaloes with 18 months of age. Semen samples were submitted to three different conditions: (CT - control) without adding medium, (SPERM) adding Sperm Talp medium, and (FERT) adding Fert Talp medium. Immediately after slaughter, both testicles from each animal were collected and transported at 4° C at maximum six hours interval. In laboratory, the removed epididymides was flushed to obtain sperm and diluted in the freezing extender. Each buffalo sperm were divided and fractions were submitted to all conditions (CT, SPERM and FERT). Semen doses were frozen at -196° C. CT, SPERM and FERT post-thawing results were 13.63±8.91, 38.77±8.91 and 42.83±8.91 for total motility, 7.30±8.74, 24.87±8.74 and 29.70±8.74 for progressive motility, 6.04±0.92, 6.74±0.92 and 6.93±0.92 for percentage of rapid cells (P < 0.05). In conclusion, diluted semen supplementation with Sperm or Fert talp increases the motility of cauda epididymal sperm of buffalo bulls.
Keywords: Buffalo; Epididymal; Freezing; Medium; Motility; Semen